2022
DOI: 10.1002/jia2.25978
|View full text |Cite
|
Sign up to set email alerts
|

“We can hardly even do it nowadays. So, what's going to happen in 5 years from now, 10 years from now?” The health and community care and support needs and preferences of older people living with HIV in Ontario, Canada: a qualitative study

Abstract: Introduction The population of people living with HIV (PLWH) is ageing consequent to effective treatment and a steady stream of new diagnoses among older adults. PLWH experience a greater burden of age‐related comorbidities and poorer social determinants of health compared to their HIV‐negative peers, yet comprehensive requisites for care and support as PLWH age remain poorly understood. Preferences And Needs for Ageing Care among HIV‐positive Elderly people in Ontario, Canada (PANACHE ON), explored the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Additionally, we found evidence that one in five participants experienced recent food insecurity, which was strongly associated with a lower quality of life. These findings are consistent with previous research describing economic insecurity and the ability to meet basic needs among older people living with HIV [41, 57, 58] and indicate that existing social supports do not adequately support the financial needs within this population. Although numerous challenges related to addressing economic and financial hardships exist, many of the stressors experienced by older people living with HIV could be addressed by increasing awareness and supporting access to existing services, including as financial support for people with low incomes and aged care services.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, we found evidence that one in five participants experienced recent food insecurity, which was strongly associated with a lower quality of life. These findings are consistent with previous research describing economic insecurity and the ability to meet basic needs among older people living with HIV [41, 57, 58] and indicate that existing social supports do not adequately support the financial needs within this population. Although numerous challenges related to addressing economic and financial hardships exist, many of the stressors experienced by older people living with HIV could be addressed by increasing awareness and supporting access to existing services, including as financial support for people with low incomes and aged care services.…”
Section: Discussionsupporting
confidence: 91%
“…These findings have important implications because, for the first time, a significant cohort of people living with HIV will need to access aged care services, either in the home or through aged care facilities. Anxieties among people living with HIV related to accessing non-judgmental and high-quality HIV care in aged care facilities with limited experience of people living with HIV have been previously identified through qualitative studies with older people living with HIV in Australia and Canada [16,41]. People living with HIV commonly report experiences of stigma in a number of settings [42][43][44], with fear of HIV transmission a key driver of HIV stigma in healthcare and workplace settings [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Age was an independent risk factor that was significantly associated with the physical health of PLWH, which was similar to other studies ( 69 , 70 ) but different from George's research ( 21 ). It may be that older PLWH experience a greater burden of age-related comorbidities, poorer social determinants of health and even ageism ( 71 ). Murzin's team ( 71 ) showed that ageism transcended multiple interactions and environments from dating to healthcare and community services to society because of social determinants, health provider issues and structural challenges.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that older PLWH experience a greater burden of age-related comorbidities, poorer social determinants of health and even ageism ( 71 ). Murzin's team ( 71 ) showed that ageism transcended multiple interactions and environments from dating to healthcare and community services to society because of social determinants, health provider issues and structural challenges. Therefore, we suggest that the government should pay more attention to older people, especially in the advent of an aging society.…”
Section: Discussionmentioning
confidence: 99%
“…In their papers, Murzin et al. [ 28 ] and Reynolds et al. [ 29 ] use qualitative methods to better understand the health needs of older PWH in marginalized and rural communities from two diverse economies: Canada and Uganda.…”
mentioning
confidence: 99%